Healing Touch: Experiencing Christ in the Age of Homo-Digitalis in a South African urban Pentecostal context - Mahlangu, Solomon Sipho (Stellenbosch Theological Journal, 2025)
In an age increasingly mediated by digital technology, this article explores how South African Pentecostal churches engage with digital faith practices, particularly regarding healing, presence, and embodiment. Rooted in ecclesial theology and African Pentecostal spirituality, the study investigates how the healing touch of Christ – symbolised in the biblical account of the woman who touched Jesus’ garment (Mk 5:25–34) – is reimagined in digital worship contexts. The central research question guiding the inquiry asks: How does digital technology impact the theological understanding of embodied faith and healing in an urban South African Pentecostal-Christian context? Drawing on qualitative reflections from pastoral workshops, theological literature, and contextual African theology, the article examines themes such as virtual sacraments, online discipleship, and AI-assisted ministry. This approach highlights both the transformative possibilities and ethical tensions of digital spirituality, encouraging a hybrid model of faith formation that honours traditional Pentecostal commitments while embracing technological innovation.